Talk to me [videorecording (Blu-Ray + DVD)] - Philippou, Danny; Hinzman, Bill; Wilde, Sophie; Otto, Miranda; Dhanji, Otis; Jensen, Alexandra; Bird, Joe; Johnson, Marcus (Actor); Terakes, Zoe; Alosio, Chris (Lionsgate, 2023)
When a group of friends discover how to conjure spirits using an embalmed hand, they become hooked on the new thrill, until one of them goes too far and opens the door to the spirit world forcing them to choose who to trust: the dead or the living.